Evaluation of spray impact on a sphere with a two-fluid nozzle. (February 2020) - Strob, Ramona; Babaria, Tejas; Rodeck, Matthias; Schaldach, Gerhard; Walzel, Peter; Thommes, Markus
Abstract: The generation of a secondary aerosol after impact, consisting of smaller droplets at a given velocity and mass flow, is relevant for various applications. Thus far, the investigations and modelling approaches on spray impact are based on extrapolation of the single-droplet impingement or empirical correlations. The validity of the models presented is limited to the given experimental setup and conditions such as initial droplet size, velocity and the impact surface characteristics. The aim of this work was to empirically evaluate the spray impact of a two-fluid nozzle on a sphere. A small-scale nozzle was used, which produced a primary aerosol with a mass median diameter of about 12 μ m (liquid-to-gas mass flow ratio = 1, gas pressure: ΔpG = 5 bar). After impact on a sphere, a multimodal distribution was observed and a higher mass flowrate of droplets in the small micrometer range ( 2 and 3 μ m ) was produced for a liquid mass flow rate in the range of 1.2–6 kg/h and an atomizing gas mass flow rate of 1–4 kg/h. For easier observation, a geometrically similar, larger nozzle was used, which produced an aerosol with a mass median diameter of about 80 μ m (liquid-to-gas mass flow ratio = 4, gas pressure: ΔpG = 1 bar). The measured droplet size after impact is smaller for a lower liquid-to-gas mass flow ratio and increased atomizing gas inlet pressure. Droplet formation mechanisms such as splashing, crown formation and spreading on the sphere surface were observed. A characteristic film with large variations in thickness was generated. Highlights: Spray-impact is combined with a two-fluid nozzle. The mass of droplets in the small micrometer range was increased during spray-impact. Droplet formation mechanisms such as splashing, crown formation and spreading on the sphere were observed.